2012
DOI: 10.2466/05.22.11.pr0.111.4.64-74
|View full text |Cite
|
Sign up to set email alerts
|

Physical Imitation and Verbal Description of Modeled Movements Engage Different Encoding Processes

Abstract: The present study analyzed the effects of performing a specified sequence of movements in imitation of a model, and examined the characteristics of the encoding involved in the process. Thirty-two college students were presented with a movement model that consisted of five elements and performed imitation tasks in which they either reproduced the movement sequence physically or described it verbally. During the period from the onset of the movement model to the imitation response, participants performed articu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In our experiments, the role of color at the output was examined. On the other hand, one study has reported that visuospatial and verbal information processing occurred during both input and output (Mizuguchi et al, 2012). Concretely, visuospatial tracks of the presented actions could have been followed and converted into verbal information, and rehearsals could have been repeated nonverbally until the output.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our experiments, the role of color at the output was examined. On the other hand, one study has reported that visuospatial and verbal information processing occurred during both input and output (Mizuguchi et al, 2012). Concretely, visuospatial tracks of the presented actions could have been followed and converted into verbal information, and rehearsals could have been repeated nonverbally until the output.…”
Section: Discussionmentioning
confidence: 99%
“…Although GOADI was originally based on studies of imitation learning in young children, it is now believed to be more generally applicable, and experiments have been conducted with both healthy adults (Bird, Brindley, Leighton, & Heyes, 2007;Brass, Bekkering, Wohlschla¨ger, & Prinz, 2000;Iacoboni et al, 2001;Koski et al, 2002;Leighton, Bird, & Heyes, 2010;Longo, Kosobud, & Bertenthal, 2008;Mizuguchi, Sugimura, & Deguchi, 2012;Newman-Norlund, Noordzij, Meulenbroek, & Bekkering, 2007;Newman-Norlund, van Schie, van Hoek, Cuijpers, & Bekkering, 2010;Wohlschla¨ger et al, 2003) and people with autism spectrum disorders (Gowen, 2012;Hamilton, 2008Hamilton, , 2009Hamilton, Brindley, & Frith, 2007;Hobson & Hobson, 2008;Vivanti et al, 2011;Wild, Poliakoff, Jerrison, & Gowen, 2012;Williams et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This indicated that it makes no specific difference whether a target action is converted into movement or is converted into language following visual input. In contrast, [23] used a dual-task method and found that for adults the movement conversion and language conversion involved different mechanisms. Thus, research about imitation by children supports the generalist hypothesis in this study; however imitation by adults did not support all aspects of the generalist hypothesis.…”
Section: Discussionmentioning
confidence: 99%